Tiroidites autoimunes - Melo, M (2006)
The term autoimmune thyroiditis encompasses a group of high prevalence thyroid disorders, which have been classified in different ways throughout the years. In this article some aspects related to its classification, epidemiology, susceptibility factors, pathogenesis, histology, diagnosis and treatment are reviewed. Some comments on the similar pathogenesis of Graves' disease are also made.